Peduncles elicit large-mammal endozoochory in a dry-fruited plant. - Zhou, Y; Newman, C; Xie, Z; Macdonald, D (2013)
BACKGROUND AND AIMS: Plants have evolved a variety of seed dispersal mechanisms to overcome lack of mobility. Many species embed seeds in fleshy pulp to elicit endozoochory, i.e. disseminating seed through the animal gut. In contrast to well-studied fleshy fruited plants, dry-fruited plants may exploit this dispersal mutualism by producing fleshy appendages as a nutritional reward to entice animals to swallow their diaspores, but this has been little studied. In this study, it is hypothesized that these accessory fruits represent co-adaptations facilitating the syndrome of mammalian endozoochorous dispersal. METHODS: Field observations (focal tree watches, faecal surveys and fruiting phenology) with experimental manipulations (examination of seed germination and feeding trials) were conducted over 2 years in a native population of the raisin tree, Hovenia dulcis, which produces enlarged, twisted brown peduncles with external black seeds, in central China. KEY RESULTS: Birds were not observed to swallow seeds or carry infructescences away during 190 h of focal tree watches. However, H. dulcis seeds were detected in 247 faecal samples, representative of two herbivore and four carnivore mammalian species. Feeding trials revealed that peduncles attracted mammals to consume the entire infructescence, thereby facilitating effective seed dispersal. The germination rate of egested seeds proved higher than that of unconsumed seeds. It was also noted that this mutualism was most vulnerable in degraded forest. CONCLUSIONS: Hovenia dulcis peduncle sets are confirmed to adapt primarily to mammalian endozoochory, a mutualistic association similar in function to fleshy pulp or foliage. This demonstrates that plant organ systems can be adapted to unique mutualisms that utilize animal dispersal agents. Such an ecological role has until now been attributed only to bird epizoochory. Future studies should consider more widely the putative role of peduncle sets and mammalian endozoochory as a dispersal mechanism, particularly for those plants that possess relatively large accessory fruits.